2017
DOI: 10.1002/clc.22658
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and long‐term outcome of super‐responders to cardiac resynchronization therapy

Abstract: Background The level of improvement in left ventricular ejection fraction (LVEF) in super‐responders to cardiac resynchronization therapy (CRT) is exceptional. However, the long‐term prognosis remains unknown in a large population. Hypothesis Whether super‐responders haven good long‐term outcomes. Methods We registered 347 patients with primary CRT‐D indication. Super‐response was defined by LVEF >50% at follow‐up echocardiogram. Best‐subset regression analysis identified predictors of super‐response. Endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
1
21
3
1
Order By: Relevance
“…Super-response to CRT has been previously reported to account for 15% to 30% of all patients receiving CRT. 3,5 In contrast, our study revealed that only 7.4% of CRT patients were categorized as superresponders. This is partially attributed to the strict criteria we adopted for the identification of randomization, and no severe adverse events occurred before the study was completed.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Super-response to CRT has been previously reported to account for 15% to 30% of all patients receiving CRT. 3,5 In contrast, our study revealed that only 7.4% of CRT patients were categorized as superresponders. This is partially attributed to the strict criteria we adopted for the identification of randomization, and no severe adverse events occurred before the study was completed.…”
Section: Discussioncontrasting
confidence: 79%
“…Super‐response to CRT has been previously reported to account for 15% to 30% of all patients receiving CRT . In contrast, our study revealed that only 7.4% of CRT patients were categorized as super‐responders.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Cardiac resynchronization therapy is one of the few effective approaches for treating nonischemic HF and improving LVEF, which is correlated with the improved prognosis (31). Unfortunately, however, not all patients are candidates for this therapy.…”
Section: Discussionmentioning
confidence: 99%